Sex Differences and Estrous Cycle Effects of Peripheral Serotonin-Evoked Rodent Pain Behaviors. (1st August 2018) - Kaur, Sukhbir; Benton, William L.; Tongkhuya, Sirima A.; Lopez, Cierra M.C.; Uphouse, Lynda; Averitt, Dayna L.
Highlights: Peripheral serotonin evokes greater and longer lasting thermal hyperalgesia in female rats during proestrus and estrus. Peripheral serotonin only evokes mechanical allodynia in female rats in proestrus and estrus. No sex differences or estrous effects were observed in edema or 5HT content in interstitial fluid of CFA-inflamed hindpaws. Local injection of the 5HT2A receptor antagonist M100907 blocked 5HT-evoked pain behaviors in cycling female and male rats. Abstract: Many persistent pain conditions occur predominantly in women making pain a major women's health issue. One theory for the prevalence in females is hormone modulation of pain mechanisms. The peripheral release of the neurotransmitter serotonin (5HT) has been implicated in various sexually dimorphic pain conditions; yet no studies have examined the effect of ovarian hormones on peripheral 5HT-evoked pain behaviors. We hypothesized that peripheral 5HT evokes greater pain behaviors in female rodents during estrus and/or proestrus, stages of the estrous cycle where ovarian hormones are greatly fluctuating. Female Sprague–Dawley rats (250–350 g) from each stage of the estrous cycle, ovariectomized females, and intact males received an intraplantar hindpaw injection of 5HT (2 μg/100 μL) or saline ( n  = 6 per group) and thermal hyperalgesia, mechanical allodynia, or edema was measured at 0, 10, 20 and 30 min post-injection. A separate group of rats received an ipsilateral injection of the selective 5HT2A antagonist, M100907, 15 min prior to 5HT injection. We report that females in proestrus and estrus exhibited significantly greater and/or longer lasting pain behaviors compared to males, females in diestrus, and ovariectomized females. There were no significant sex differences or estrous cycle effects on 5HT-evoked edema or 5HT content in inflamed hindpaws. Local pretreatment with the 5HT2A receptor antagonist blocked 5HT-evoked thermal hyperalgesia and edema. These data provide evidence of a modulatory role of hormones on peripheral 5HT-evoked pain occurring via the 5HT2A receptor.